Deposition and characterisation of carbon thin films via patented Off-Plane Double Bend FCVA deposition system - Lee, Jin Zhou (Nanyang Technological University, 2022)
In this project, carbon thin films that are deposited by Off-Plane Double Bend (OPDB) Filtered Cathodic Vacuum Arc (FCVA) system are characterised. By varying the substrate temperature and voltage bias of the FCVA system, different types of carbon thin film can be obtained. Tetrahedral amorphous carbon (ta-C) thin films have properties such as hardness and electrical insulator while nano-crystalline graphitic (NCG) carbon thin film has improved electrical conductivity in the vertical direction normal to the substrate. The formation of NCG carbon thin film can be achieved by applying compressive stress and activation energy to the substrate. The carbon thin films are characterised using Raman spectroscopy and the I-V probe station to understand the composition of the carbon thin film as well as its electrical properties. Results from the Raman curve fitting show that NCG carbon thin films can either be obtained at voltage bias set from 0V to -100V with a substrate temperature of 600°C or -400V at RT. On the other hand, ta-C thin films can be obtained by setting the voltage bias at -50V to -100V so long as the substrate temperature is set at room temperature (RT) range (10°C to RT). I-V results show that NCG carbon thin film has superior electrical conductivity compared to a-C thin films and this brings many possible applications for NCG carbon thin film where high electrical conductivity is required.